Innovative methodology for the assessment of thermal comfort and climate resilience in social housing in Coahuila, Mexico - Gómez de León, Ana Berenice (2022)
Social housing in Mexico comprises of a repetitive design that does not respond to local climate. The scarce studies regarding thermal comfort combined with the use of accurate weather files represented a gap in knowledge that led to the development of the current research. Three locations for the state of Coahuila, a northeast state of the country, were considered for their analysis: Saltillo, Monclova and Torreón. These cities were selected because even if they are in the same state, have three different climates. Weather files for future climate scenarios are not available for the mentioned cities, as is also the case for many locations in the country.